Do We Have to Get Along to Innovate? The Influence of Multilevel Social Cohesion on New Product and New Service Development. Issue 6 (5th July 2016) - Shaner, Matthew B.; Beeler, Lisa; Noble, Charles H.
Abstract : In this study, based on the Comparative Performance Assessment Study survey conducted by the Product Development Management Association, the authors develop and test a model which considers the antecedents and performance outcomes of social cohesion, a seemingly critical organizational factor in new product development (NPD). Using a sample of over 450 innovation and product development professionals from North America, Europe, and Asia, social cohesion is conceptualized and tested across three levels—within team cohesion, between team cohesion, and between firm cohesion. The results of a structural equation model indicate several differences between the antecedents of the varying forms of social cohesion. A post hoc exploration of the difference between goods‐ versus service‐dominant firms provides a clearer picture of cohesion's influence on innovation outcomes. Specifically, within team and between team cohesion are positively associated with new services performance, while for traditional goods‐based NPD, within team, between team, and between firm cohesion all appear to be positively related to performance. The findings suggest that high social cohesion is not always optimal and that managers should focus on specific types or levels of social cohesion as opposed to thinking about social cohesion as a one‐dimensional construct. The findings also suggest that goods‐ and service‐centric firms can use different tactics or strategies to drive social cohesion and, ultimately, new product performance, and that innovation managers may need to allocate resources differently depending on the nature of the market offering being developed. The paper also presents several implications for theory and practice, as well as future research directions related to the various levels of social cohesion and their influence on new product and new service performance.